2019
DOI: 10.4028/www.scientific.net/msf.945.238
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Composite Gypsum Binders Depending on Multicomponent Mineral Additives

Abstract: This article considers the possibility of increasing the effectiveness of composite gypsum binders (CGB) by controlling the processes of structure formation as a result of using new types of multicomponent mineral additives that are significantly different from the traditionally used quartz raw materials:- waste of wet magnetic separation of ferrous quartzites (WMS waste,) of polymineral composition with quartzy of varying degrees of crystallinity, nanodispersed silica and chalk powder. We have studied the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The obtained data on the strength characteristics and water resistance of modi ed gypsum binders based on synthetic gypsum derived from wastes are very similar to those obtained on the basis of natural raw materials (Lesovik et al, 2019). From the results obtained, we concluded that synthetic materials obtained from water treatment coagulation sediment and spent sulfuric acid, are a promising analogue of materials obtained on the basis of natural minerals.…”
Section: Determination Of the Composition Of Additives Of Complex Act...supporting
confidence: 71%
“…The obtained data on the strength characteristics and water resistance of modi ed gypsum binders based on synthetic gypsum derived from wastes are very similar to those obtained on the basis of natural raw materials (Lesovik et al, 2019). From the results obtained, we concluded that synthetic materials obtained from water treatment coagulation sediment and spent sulfuric acid, are a promising analogue of materials obtained on the basis of natural minerals.…”
Section: Determination Of the Composition Of Additives Of Complex Act...supporting
confidence: 71%